13.1k views
3 votes
If f(x) = -5x - 1 and g(x) = x - 6 what is (f g) (7)

User H Sampat
by
5.3k points

2 Answers

5 votes

You have


(f\circ g)(x) = f(g(x)) \implies (f\circ g)(7) = f(g(7))

So, we have to compute g(7) and feed it as input to f(x). We have


g(7)=7-6=1 \implies f(g(7))=f(1)=-5-1=-6

User Thatzprem
by
5.6k points
0 votes

Answer:

-6

Explanation:

I just took it and got it right ☺

User Hettie
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.